An Analysis of Inflectional and Derivational Affixes on Psalms Chapters 1-10 From the Bible King James Version - Samosir, Nelly Elisabeth; Pasaribu, Rotua Elfrida; Sembiring, Rony Arahta (Tamaddun Life, 2023)
The objective of this study is to identify the inflectional and derivational affixes present in Psalms chapters 1-10 of the King James Version, and to examine the manner in which these affixes are processed. This study employs a qualitative research approach characterized by a descriptive design. When examining the data, the author emphasizes the inflectional and derivational affixes found in the King James translation of the Bible, as outlined by Katamba's theory (1993:40) that states "derivation and inflection are two distinct methods of constructing words." The word formation mechanisms mentioned here can be categorized into two primary types of affix morphemes: derivational affixes and inflectional affixes. The study identified a total of 49 derivational affixes, consisting of 10 prefixes (8.20%), 39 suffixes (31.59%), and 73 inflectional affixes (59.84%). According to the findings of this study, the processing of inflectional affixes is more prevalent than that of derivational affixes when examining the text of Psalms in the King James translation, namely chapters 1-10. The dominance of the suffixes -ed/-d/-ied is due to the prevalence of past tense sentences in the text. This study can serve as a valuable resource for lecturers, particularly those teaching morphology, since it provides clear differentiation between roots and affixes, enabling a comprehensive understanding of the word formation process and the significance of affixes. This study can assist other scholars in analyzing the formation of derivational and inflectional affixes and their processes. This study can serve as a valuable resource for studying vocabulary and word building. Additionally, the study has broader implications, serving as a foundational reference for morphology education, linguistic analysis, and interdisciplinary studies. It enriches our understanding of the linguistic characteristics of the King James Bible, offering insights into the intricate dynamics of word formation within religious texts.